Analisis Metode Kalman Filter, Particle Filter dan Correlation Filter Untuk Pelacakan Objek - Sholehurrohman, Ridho; Habibi, Mochammad Reza; Ilman, Igit Sabda; Taufiq, Rahman; Muhaqiqin, Muhaqiqin (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
Object tracking is a challenging in computer vision. Object tracking is divided into two, which can be one object or several objects, depending on the object being observed. The process of tracking an object in the form of one object is to estimate the target in the next sequence based on information from the first frame given. In object tracking in the form of single object tracking, there are five steps that are often used in discriminatory methods, including motion models, feature extraction, observation models, model updates and integration methods. Although various algorithms of object tracking are proposed, there are still failures in the object tracking process caused by occlusion, non-rigid target deformation, and other factors. This study proposes the implementation of the Kalman filter, particle filter, and correlation filter methods for object tracking in video data. The results of the implementation of the three methods can track objects in traffic video data and the script circuit video. In object tracking calculations and method analysis, the kalman filter gets 96.89% where the kalman method is better in terms of accuracy compared to other methods. Meanwhile, in the average performance of computation time, the correlation method gets 26.69 FPS, where the correlation method is superior compared to other competitor methods. Keywords – Kalman Filter; Particle Filter; Correlation Filter; Object Tracking; Object Tracking in Video